Improvement of ship stability and safety in intact condition through operational measures: challenges and opportunities. (1st July 2016) - Bačkalov, Igor; Bulian, Gabriele; Rosén, Anders; Shigunov, Vladimir; Themelis, Nikolaos
Abstract: Attaining a sufficient level of safety from the point of view of stability is typically considered to be a matter of design. However, it is impossible to ensure safety only by design measures, and operational measures can then represent a complementary tool for efficiently and cost-effectively increasing the overall safety of the vessel. Time could therefore be coming for systematically considering operational measures as a recognised and regulated integral part of a holistic approach to ship safety from the point of view of stability. This paper therefore aims at capturing recent trends of research targeting operational safety measures, with specific attention to the intact ship condition. Open challenges and opportunities for research are identified, potential benefits and shortcomings of different options are discussed, and needs and possibilities for further developments in this area are explored. As an overall goal, this paper aims at providing food for thoughts as well as a ground for further proceeding towards the target of implementing a virtuous integrated approach to intact ship safety, from the point of view of stability, which gives due credit to effective and robust operational risk control options. Highlights: Operational measures can effectively complement design measures in increasing ship safety. Recent trends of research targeting operational safety measures are identified. Intact ship condition is specifically addressed. Discussion is separately given for: design, regulatory and classification aspects; tools and methodologies; implementation in operation. Needs, opportunities, and open challenges are identified in view of future developments.